LncRNA HOXA-AS3 promotes gastric cancer progression by regulating miR-29a-3p/LTβR and activating NF-κB signaling - Feng Qu; Bin Zhu; Yi-Lin Hu; Qin-Sheng Mao; Ying Feng (Cancer Cell International, 2021)
Abstract Background Gastric cancer (GC) is among the most common and deadliest cancers globally. Many long non-coding RNAs (lncRNAs) are key regulators of GC pathogenesis. This study aimed to define the role of HOXA-AS3 in this oncogenic context. Methods Levels of HOXA-AS3 expression in GC were quantified via qPCR. The effects of HOXA-AS3 knockdown on GC cells function were evaluated in vitro using colony formation assays, wound healing assays and transwell assays. Subcutaneous xenograft and tail vein injection tumor model systems were generated in nude mice to assess the effects of this lncRNA in vivo. The localization of HOXA-AS3 within cells was confirmed by subcellular fractionation, and predicted microRNA (miRNA) targets of this lncRNA and its ability to modulate downstream NF-κB signaling in GC cells were evaluated via luciferase-reporter assays, immunofluorescent staining, and western blotting. Results GC cells and tissues exhibited significant HOXA-AS3 upregulation (P < 0.05), and the levels of this lncRNA were found to be correlated with tumor size, lymph node status, invasion depth, and Helicobacter pylori infection status. Knocking down HOXA-AS3 disrupted GC cell proliferation, migration, and invasion in vitro and tumor metastasis in vivo. At a mechanistic level, we found that HOXA-AS3 was able to sequester miR-29a-3p, thereby regulating the expression of LTβR and modulating NF-κB signaling in GC. Conclusion HOXA-AS3/miR-29a-3p/LTβR/NF-κB regulatory axis contributes to the progression of GC, thereby offering novel target for the prognosis and treatment of GC.